Exploring the predictive properties of the Hayes Ability Screening Index subtest background information in identifying individuals with MBID among in-patients with SUD - Braatveit, Kirsten J.; Assmus, Jörg; Hove, Oddbjørn (Frontiers in Psychiatry, 2022)
Background: Mild to borderline intellectual disability (MBID) go undetected in treatment clinics for individuals with substance use disorder (SUD). The Hayes Ability Screening Index (HASI) is found to be a valid, timesaving screening instrument for MBID in SUD treatment. MBID can have significant implication for treatment planning and outcomes. It is therefore important to have methods for early recognition of these comorbid conditions. Due to less sensitivity of recent or ongoing substance use, the HASI subtest background information may be particularly valuable as an early screening of MBID. However, little is known about the subtests single predictive abilities for patients with SUD, or in comparison to the other subtests of the HASI. Aims: The main aim was to investigate the convergent, predictive and discriminant validity of the individual HASI subtests, with special interest in background information, in identifying inpatients with SUD as MBID or no-MBID. Methods: Eighty-four SUD in-patients aged 19-64 participated in this multicentre study. MBID was diagnosed according to the ICD-10 using WAIS-IV, Vineland II, and self-reported childhood learning difficulties. Results: The main finding was that the HASI subtests background information and puzzle predicts classification of MBID, with background information being the strongest predictor. A HASI background information cut between 6 and 7 showed a sensitivity 78% and specificity of 72%. Conclusion: The HASI subtest background information has acceptable convergent, predictive and discriminant validity as a screening for MBID among inpatients in SUD treatment.